Mitigating the environmental impact of NSAIDs - physiotherapy as a contribution to One Health and the SDGs. (2nd January 2023) - Banerjee, Srishti; Maric, Filip
Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) continue to be amongst the most frequently used pharmaceutical treatments for mild to moderate musculoskeletal pain globally. In this short communication, we continue to expand the growing field of environmental physiotherapy by tracing NSAIDs journey through aquatic ecosystems, and the potential of physiotherapy to mitigate these negative environmental impacts and so contribute to achieving a range of UN Agenda 2030 Sustainable Development Goals and the aspirations of One Health. Through metabolic excretion into waterways, NSAIDs negatively impact the health and survival of various aquatic lifeforms, which, in turn, has consequences for human health. By reducing and delaying the need for pharmacotherapy for mild to moderate musculoskeletal pain, physiotherapy presents an important sustainable healthcare solution. Beyond this, however, the ecological persistence of NSAIDs also underscores the need for transformative change in healthcare and physiotherapy, towards the full recognition of the interconnected nature of human, animal, and ecosystems health and the complex questions and responsibilities this raises. For this, we need to increase our understanding of the entangled nature of health and its negotiation with human and non-human others and develop approaches to include them in our thinking, pursuit, and practice of health and care.